Multi-view co-attention network for fake news detection by modeling topic-specific user and news source credibility. Issue 1 (January 2023) - Bazmi, Parisa; Asadpour, Masoud; Shakery, Azadeh
Highlight: We are the first to define topic-specific user credibility based on his socio-cognitive bias and use it for fake news detection. We present a novel variant of the co-Att mechanism to implicitly model the credibility of users and news sources. We produce great echo-chamber representation by using BiCM and user news sharing behaviors. A novel heterogeneous graph is proposed to jointly model news media partisan bias and level of bias with weak supervision. Our model employs knowledge entities in the news in addition to the partisan bias of its source for more effective representation of news political ideology. Abstract: The wide spread of fake news and its negative impacts on society has attracted a lot of attention to fake news detection. In existing fake news detection methods, particular attention has been paid to the credibility of the users sharing the news on social media, and the news sources based on their level of participation in fake news dissemination. However, these methods have ignored the important role of news topical perspectives (like political viewpoint) in users'/sources' decisions to share/publish the news. These decisions are associated with the viewpoints shared by the echo-chamber that the users belong to, i.e., users' Socio-Cognitive (SC) biases, and the news sources' partisan bias. Therefore, the credibility of users and news sources are varied in different topics according to the mentioned biases; which are completely ignored in current fake news detection studies. In this paper, we propose a Multi-View Co-Attention Network (MVCAN) that jointly models the latent topic-specific credibility of users and news sources for fake news detection. The key idea is to represent news articles, users, and news sources in a way that the topical viewpoints of news articles, SC biases of users which determines the users' viewpoints in sharing news, and the partisan bias of news sources are encoded as vectors. Then a novel variant of the Multi-Head Co-Attention (MHCA) mechanism is proposed to encode the joint interaction from different views, including news-source and news-user to implicitly model the credibility of users and the news sources based on their interaction in real and fake news spreading on the news topic. We conduct extensive experiments on two public datasets. The results show that MVCAN significantly outperforms other state-of-the-art methods and outperforms the best baselines by 3% on average in terms of F1 and Accuracy.